Entitlement, Job Performance, and Flourishing Among Nurses: An International Mediation Analysis Study - Emad Adel Shdaifat PhD; Amira Alshowkan PhD (SAGE Open Nursing)
Objective To examine the mediating role of job performance in the relationship between employee entitlement and flourishing among nurses in Saudi Arabia and Jordan. Methods A cross-sectional study was conducted in government hospitals located in eastern Saudi Arabia and northern Jordan. Utilizing convenience sampling, data were collected from a sample of 437 nurses. The instruments employed in this study included the Flourishing Index, the Job Performance Scale, and the Employee Entitlement Scale. Results In Saudi Arabia, the model accounted for 15.9% of the variance in flourishing and 7.1% in performance. In Jordan, the model explained 15.2% of flourishing but only 4.3% of performance. Mediation analysis revealed that entitlement exerted an indirect influence on flourishing through performance in both countries (Saudi Arabia: indirect effect = 0.107, p  < .001; Jordan: indirect effect = 0.062), with a fully mediated effect observed in Jordan. Conclusion Job performance serves as a mediating factor between entitlement and flourishing among nurses. These findings provide valuable insights for healthcare administrators and policymakers seeking to improve nurse well-being through targeted performance support interventions.